Quantitative trait loci underlying soybean seed tocopherol content with main additive, epistatic and QTL × environment effects. (10th October 2017) - Liu, Huancheng; Cao, Guanglu; Wu, Depeng; Jiang, Zhenfeng; Han, Yingpeng; Li, Wenbin
Abstract: Soybean ( Glycine max [L.] Merrill) seeds are a major source of tocopherols (Toc), which could significantly improve immune system health of human and prevent or treat many serious diseases. Selection for higher Toc contents of seeds could increase nutritional value of soybean‐derived food, laying on an important breeding goal for many soybean breeders. The present objectives of the work were to evaluate various genetic effects of QTL associated with individual and total Toc content based on a RIL population ("Beifeng 9" × "Freeborn") in six environments to improve the efficiency of molecular marker‐assisted selection (MAS) for high‐Toc breeding. The results described that eighteen, thirteen, eleven and thirteen QTL were associated with α‐Toc, γ‐Toc, δ‐Toc and total Toc content, respectively, and have additive main effects ( a ) and/or additive × environment interaction effects ( ae ) in certain environments. Among them, four QTL for α‐Toc, two QTL for γ‐Toc, one QTL for δ‐Toc and four QTL for total Toc could increase α‐Toc, γ‐Toc, δ‐Toc and total Toc content via significant a effect, respectively, which have stronger stability in different years and locations. It implied a value for MAS. Additionally, twenty‐five, fifteen, eleven and twenty epistatic pairwise QTL associated with α‐Toc, γ‐Toc, δ‐Toc and total Toc contents, respectively, were detected. The genetic information of the QTL effects obtained here would be beneficial for breeding soybean variety with high‐Toc content by MAS.